Electromagnetic Band-Gaps Structure In Microwave Device Design - A. Rahim, Mohamad Kamal (Faculty of Electrical Engineering, 2008)
The research in the field of electromagnetic band gap or well known as EBG structure has becoming attractive in antenna community. This structure has a unique property such as the ability to suppress the propagation of surface wave in specific operating frequency defined by the EBG structure itself. The electromagnetic band gap structure always used as a part of antenna structure in order to improve the performance of the antenna especially for improves the gain and radiation pattern. In this project, microstrip antenna is used due to the advantages such as easy and cheap fabrication, light weight, low profile and can easily integrated with microwave circuit. This project involves the investigation of various EBG structure and the integration of the EBG structure with various antenna design through the simulation and fabrication process. The simulation is done by using microwave office software (MWO) and CST. The fabrication process involves the photo etching technique while the substrate used for antenna fabrication is FR4 board which has relative permittivity 4.7 and tangent loss 0.019. From the simulation done, most of the antenna which has been incorporated with EBG structure show the enhancement of the performance in term of radiation pattern, gain and return loss, S11. The 1 dB gain increment is noticed for microstrip array antenna with incorporated with EBG structure. The radiation pattern also improves where the side and back lobes are decreasing by using EBG structure surrounding the patch antenna. Other than that, the EBG structure also can be used as a band reject especially for ultra wide band application which operates at very wide frequency ranges. The simulation and measurement result for ultra wide band with and without band rejection has been shown in this thesis.